2022
DOI: 10.1039/d1cs00556a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic control over site-selectivity in hydrogen atom transfer (HAT) based C(sp3)–H functionalization promoted by electrophilic reagents

Abstract: Leveraging on electronic effects in both the substrate and HAT reagent, site-selectivity can be implemented in C(sp3)–H bond functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 198 publications
(267 reference statements)
1
89
0
Order By: Relevance
“…Moreover, heterocyclic substrates containing oxygen ( 46 , 56% yield) and nitrogen ( 47 , 45% yield) atoms could be selectively functionalized on a position distal from the heteroatom, which is challenging via HAT. 10 Additionally, because of the mild conditions of the process, we were able to selectively functionalize 1,3-dibromoadamantane on only a single position ( 48 , 67% yield). We also found that vinylboronic acid pinacol ester could be smoothly engaged in the reaction protocol ( 49 , 72% yield).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heterocyclic substrates containing oxygen ( 46 , 56% yield) and nitrogen ( 47 , 45% yield) atoms could be selectively functionalized on a position distal from the heteroatom, which is challenging via HAT. 10 Additionally, because of the mild conditions of the process, we were able to selectively functionalize 1,3-dibromoadamantane on only a single position ( 48 , 67% yield). We also found that vinylboronic acid pinacol ester could be smoothly engaged in the reaction protocol ( 49 , 72% yield).…”
Section: Resultsmentioning
confidence: 99%
“… 9 The selectivity of such HAT processes depends on the careful balance between electronic and steric properties of the substrates and the reaction conditions. 10 In parallel to HAT, halogen atom transfer (XAT) 11 has been used in metallaphotoredox manifolds as well, 12 , 13 enabling the use of alkyl halides as radical precursors. This method relies on the photocatalytic generation of silicon-centered 12 or α-amino 13 radicals, which induce homolytic cleavage of the C–X (X: halogen) bond.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient strategies for selective functionalization of the (sp 3 )C–H bond will help people to exploit the alkane sources on Earth more effectively and cleanly. 4 Interestingly, several elegant methods for direct radical alkylation/arylation of the (sp 3 )C–H bond with organoboronic acids have been developed independently by Lei, Huo and Liu. 5 In 2013, Lei and co-workers reported a first example of this conversion via Ni( ii )-catalysis.…”
Section: Free-radical Alkylation/arylation Of the (Sp3)c–h Bond With ...mentioning
confidence: 99%
“…and medium-dependent effects (e. g., hydrogen-atom abstractor, additives, solvent, etc.). [8][9][10][11][12] However, in order to homolytically break a CÀ H bond, a considerable amount of energy (typically > 90 kcal mol À 1 ) [13] is required, which calls for the generation of aggressive intermediates. Traditional HAT involves p-block radicals such as, for example, tert-butoxyl (t-BuO * ) or cumyloxyl (CumO * ) radicals, [14][15][16] namely electrophilic O-centered radicals that can be generated via photolysis [17] of the corresponding peroxide or heating a solution containing the hydroperoxide and a catalytic amount of a transition metal (typically copper).…”
Section: Introductionmentioning
confidence: 99%